Generalized Spinous Follicular Lichen Nitidus with Perifollicular Granulomas. Issue 3 (8th July 2012) - Summe, Heather S.; Greenlaw, Sheila M.; Deng, April; Magro, Cynthia; Wiss, Karen
<x xml:space="preserve">Abstract</x> Abstract: The first report of spinous follicular lichen nitidus with perifollicular granulomas was by Madhok and Winkelmann in 1988. Since this report, a few cases of follicular or periappendageal lichen nitidus have been described, in a more localized form or without perifollicular granulomas. We describe a 5‐year‐old girl with the rare generalized spinous follicular variant of lichen nitidus with perifollicular granulomas.